Type I and Type III Interferons – Induction, Signaling, Evasion, and Application to Combat COVID-19 - Park, Annsea (Cell Host Microbe, 2020)
Coronavirus disease 2019 (COVID-19) is a global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Without approved antiviral therapeutics or vaccines to this ongoing global threat, type I and type III interferons (IFNs) are currently being evaluated for their efficacy. Both the role of IFNs and the use of recombinant IFNs in two related, highly pathogenic coronaviruses, SARS-CoV and MERS-CoV, have been controversial in terms of their protective effects in the host. In this review, we describe the recent progress in our understanding of both type I and type III IFN-mediated innate antiviral responses against human coronaviruses and discuss the potential use of IFNs as a treatment strategy for COVID-19.